Influence of post-harvest maturation on the amylolytic activity of wheat grain and the properties of bread - Szafrańska, Anna; Stępniewska, Sylwia (Polish Journal of Agronomy, 2021)
The aim of this study was to determine the quantitative and qualitative changes in the starch complex and the amylolytic activity of wheat grain during its post-harvest maturity. This in- formation is necessary for the proper determination of the level of quality requirements for wheat grain purchased immediately after harvest. The common wheat cultivars: Kandela, Bamberka and KWS Ozon were tested during this study. Because of the variability of weather conditions, three wheat cultivars were tested (two winter wheat cultivars and one spring wheat cultivar) from two consecu- tive crop years. Immediately after grain harvest and during the next 12 weeks in two-weeks intervals the falling number, amylo- graph properties, rheological properties of dough and laboratory baking test was performed. Tested wheat cultivars were characterized by low amylolytic activity. Changes of the baking value of tested wheat cultivars during their post-harvest maturation were dependent on wheat cultivar and harvest year. Wheat from the 2016 harvest was char- acterized by significantly lower amylolytic activity compared to grain from 2015 harvest. Amylolytic activity decreased during post-harvest maturation, i.e. the falling number increased as well as the dough torque in point C4 and C5 of mixolab curve. There was also an increase in the volume of bread compared to the evaluation of the samples tested immediately after harvest. The highest values were obtained in the 4th week after harvest. The changes were dependent on wheat cultivar. However, in the case of the assessment of the rheological characteristics of the dough (except point C4) they were not statistically significant.